An Update on the Function, Biosynthesis and Regulation of Floral Volatile Terpenoids - Zhenglin Qiao (MDPI AG, 2021)
Floral volatile terpenoids (FVTs) belong to a group of volatile organic compounds (VOC) that play important roles in attracting pollinators, defending against pathogens and parasites and serving as signals associated with biotic and abiotic stress responses. Although research on FVTs has been increasing, a systematic generalization is lacking. Among flowering plants used mainly for ornamental purposes, a systematic study on the production of FVTs in flowers with characteristic aromas is still limited. This paper reviews the biological functions and biosynthesis of FVTs, which may contribute a foundational aspect for future research. We highlight regulatory mechanisms that control the production of FVTs in ornamental flowers and the intersection of biosynthetic pathways that produce flower fragrance and color. Additionally, we summarize the opportunities and challenges facing FVT research in the whole genome and -omics eras and the possible research directions that will provide a foundation for further innovation and utilization of flowering ornamental plants and their germplasm resources.